Sexual health literacy level and its related factors among married medical sciences college students in an Iranian setting: a web‑based cross‑sectional study - Samaneh Nematzadeh; Zohreh Shahhosseini; Mahmood Moosazadeh; Zeinab Hamzehgardeshi (BMC, 2024)
Abstract Background Sexual health literacy (SHL) leads to the development of personal ability, understanding, evaluation and use of information related to sexual health. The purpose of this study was to assess the sexual health literacy level and its related factors among married college students at Mazandaran University of Medical Sciences (MAZUMS). Methods A web-based cross-sectional online study was conducted on married college students at Mazandaran University of Medical Sciences between January and November 2020. All students were included in the study by census, and the study method was explained by telephone. If they agreed to participate in the study, the online link to the questionnaire, including sociodemographic and clinical information and Sexual Health Literacy for Iranian Adults (SHELIA), was emailed. The Statistical Package for the Social Sciences (SPSS) software version 26 was used for data analysis. Univariate and multivariate logistic regression tests were used to assess factors related to sexual health literacy. Results The sample consisted of 277 male and 123 female students. Sexual Health Literacy Level and all subscales are at the sufficient level (66.1-88). Among the participants, 20.5% had limited sexual health literacy. Multivariate analysis found factors related to sexual health literacy among students: economic status (OR 0.03; 95% CI 0.0-0.55) and faculty (OR 0.07; 95% CI 0.01-0.52) is related to decrease and subscription to social media for sexual health (OR 3.27; 95% CI 1.53-7.01), information source of channels and cyberspace (OR 3.23; 95% CI 1.41-7.39), educational level (OR 16.39; 95% CI 2.16-32.70), Internet search information source (OR 1.91; 95% CI 1.00-3.64) is related to increase, were statistically significant factors. Conclusion In Iran, medical sciences college students, who constitute a significant portion of the country's population, are responsible for sexual health education. Government agencies, with the collaboration of all stakeholders, should develop policies and programs for implementing and evaluating integrated and comprehensive sexual health literacy promotion programs for them.